Reflections from West Germany on the Science-Fiction Market. - Hasselblatt, Dieter (Science Fiction Studies)
The article discusses Science Fiction (SF) as a commercial commodity. SF is distributed through several channels including hardcover books, paperback series, TV series, films, radio plays. In West Germany, there is genuine dramaturgy in the domain of radio plays unlike in the U.S., where for the sake of commercial profits, the quality of the manuscript is compromised.